Peningkatan Akses Pasar Bagi Pelaku Industri Kreatif Melalui Pemanfaatan Platform Digital - Maulana, M Faizal; Nisa, Faizatul Laily (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
All aspects of human life have been influenced by digital transformation, which has become a global trend ( Bangsawan, 2023 ). In Indonesia, policies that can accelerate digital transformation can accelerate economic growth, especially in the creative economy sector. To accelerate the existing transformation, infrastructure, literacy and regulation are existing problems. faster digital transformation in the development of Indonesia's creative economy. Studies show that policies that encourage digital transformation can encourage the growth of the creative economy in Indonesia, but they need to be adapted to local conditions and followed by efforts to increase the accessibility of adequate infrastructure and technology. Efforts to address existing challenges, such as improving technological accessibility and adequate infrastructure, could be part of this. Therefore, to encourage and support creative economic growth through policy, industry players, government and society must work together. accelerate the digital transformation process.